KUALITAS PAPAN KAYU MANGLID (Manglieta glauca BL.) PADA DUA POLA PENGGERGAJIAN - Mohamad Siarudin; Ary Widiyanto (Jurnal Penelitian Hasil Hutan, 2012)
This research aims to examine the quality of manglid (Manglieta glauca Bl.) sawn boards through two sawing patterns, based on the defective shape and fiber separation. Samples of manglid logs were taken from community forest in Sodongbilir village, Tasikmalaya Regency, West Java. A total of 35 sawn boards from each of live sawing pattern and semi-quarter sawing pattern were taken as specimens. The research results show that type of shape defects occurred were twisting defect (55,91%), curving defect (53,57%) and arcing defect (41,35%). In terms of the fiber separation defects, all of defect types occurred including closed rupture (18,25%), opened rupture (14,13%) and splitted (2,82%). The arcing and twisting defects are significantly different between the two sawing patterns. The curving defect, closed rupture, opened rupture, and splitting are relatively similar between the two sawing patterns. Sawn boards from live sawing pattern bave a lower arcing defect and percentage of fresh sapwood, but have a bigber curving defect than those from semi quarter sawing pattern. Based on those defective shape and fiber separation defects, sawn board exctracted from live sawing patterns show's better quality than those of semi quarter refering to the Indonesian National Standard.